Cloud model-based analysis of regional sustainable water resource utilization schemes - Qiang, Fu; Fanxiang, Meng; Tianxiao, Li; Dong, Liu; Fanli, Gong; Osman, Amgad; Yutong, Li (International Journal of Agricultural and Biological Engineering, 2016)
Given the adverse effects of current water shortages, low utilization and imbalance between the supply and demand, and other status quo problems relating to social economic development, the construction industry and agriculture, a cloud model was applied to a water resource system using five sustainable water resource utilization schemes for Kiamusze, Heilongjiang Province, as an example. This research changes the qualitative description of the concept language into a quantitative analysis of an evaluation indicator. A cloud model-based analytical method for regional sustainable water resource utilization schemes was proposed, and the sustainable grades of the water resources were calculated. The research results showed that, in addition to the natural continuation of such schemes, the development trends of four new schemes achieved the sustainable utilization of water resources, and thus, the sustainable water resource utilization was optimized. However, when the open-source, throttle, comprehensive and coordination schemes were subjected to the optimum applicability analysis, based on the limiting factors in different periods, resource availability and long-term development, decision-making regarding the best solution in different periods better ensures sustainable development in Kiamusze. The research results provide a significant theoretical basis for the formulation of scientific and reasonable sustainable water resource utilization strategies in Kiamusze. Keywords: cloud model, regional water resources, sustainable utilization, normal cloud, scheme analysis DOI: 10.3965/j.ijabe.20160905.2529 Citation: Fu Q, Meng F X, Li T X, Liu D, Gong F L, Osman A, et al. Cloud model-based analysis of regional sustainable water resource utilization schemes. Int J Agric & Biol Eng, 2016; 9(5): 67－75.